Changes in co-contraction during stair descent after manual therapy protocol in knee osteoarthritis: A pilot, single-blind, randomized study. Issue 4 (October 2016) - Cruz-Montecinos, Carlos; Flores-Cartes, Rodrigo; Montt-Rodriguez, Agustín; Pozo, Esteban; Besoaín-Saldaña, Alvaro; Horment-Lara, Giselle
Summary: Introduction: Manual therapy has shown clinical results in patients with knee osteoarthritis. However, the biomechanical aspects during functional tasks have not been explored in depth. Methods: Through surface electromyography, the medial and lateral co-contractions of the knee were measured while descending stairs, prior and posterior to applying a manual therapy protocol in the knee, with emphasis on techniques of joint mobilization and soft-tissue management. Results: Sixteen females with slight or moderate knee osteoarthritis were recruited (eight experimental, eight control). It was observed that the lateral co-contraction index of the experimental group, posterior to intervention, increased by 11.7% (p = 0.014). Conclusions: The application of a manual therapy protocol with emphasis on techniques of joint mobilization and soft-tissue management modified lateral co-contraction, which would have a protective effect on the joint.